Investigation of the performance of PID control scheme for linear conveyor system of manufacturing shopfloor - Ab Rahman, Nur Naajihah; Nafrizuan, M. Y.; Zainal Abidin, Nuril Aqilah (Penerbit UMP, 2022)
Conveyor systems have been utilized widely in the manufacturing shop floor as well as in the production line. It is ideals in enhancing productivity and maximizes the operation of a warehouse. However, the performance of the conveyor system can be influenced by a controller as well as the DC motor itself in providing the best response. Therefore, this paper will discuss the performance of the conveyor system that applied PID controller tuned by the Ziegler-Nichols tuning method. To validate the performance of the proposed controller and tuning method on the conveyor system, it will be compared with the DC motor without implement any controller as well as tested onto the prototype of the linear conveyor system. Performances from both different conditions of conveyor system will be evaluated in terms of transient response that are, rise time, settling time and time constant for the simulation part that will be done in MATLAB/Simulink software while position and time will be the other characteristics in evaluating the performance by using the hardware. At the end of the study, by considering both simulation and experimental results, the DC motor with a PID controller shows a better performance for the conveyor system compared to the DC motor without applying any controller.